Impact of Maternal Environment and Inflammation on Fetal Neurodevelopment - Chiara Lubrano; Francesca Parisi; Irene Cetin (MDPI AG, 2024)
During intrauterine life, external stimuli including maternal nutrition, lifestyle, socioeconomic conditions, anxiety, stress, and air pollution can significantly impact fetal development. The human brain structures begin to form in the early weeks of gestation and continue to grow and mature throughout pregnancy. This review aims to assess, based on the latest research, the impact of environmental factors on fetal and neonatal brain development, showing that oxidative stress and inflammation are implied as a common factor for most of the stressors. Environmental insults can induce a maternal inflammatory state and modify nutrient supply to the fetus, possibly through epigenetic mechanisms, leading to significant consequences for brain morphogenesis and neurological outcomes. These risk factors are often synergic and mutually reinforcing. Fetal growth restriction and preterm birth represent paradigms of intrauterine reduced nutrient supply and inflammation, respectively. These mechanisms can lead to an increase in free radicals and, consequently, oxidative stress, with well-known adverse effects on the offspring's neurodevelopment. Therefore, a healthy intrauterine environment is a critical factor in supporting normal fetal brain development. Hence, healthcare professionals and clinicians should implement effective interventions to prevent and reduce modifiable risk factors associated with an increased inflammatory state and decreased nutrient supply during pregnancy.